Volicitin, an elicitor of maize volatiles in oral secretion of Spodoptera exigua: Isolation and bioactivity - Turlings, Ted; Alborn, Hans; Loughrin, John H; Tumlinson, James H (My University, 2000)
Plants respond to insect-inflicted injury by systemically releasing relatively large amounts of several volatile compounds, mostly terpenoids and indole. As a result, the plants become highly attractive to natural enemies of the herbivorous insects. In maize, this systemic response can be induced by the uptake via the stem of an elicitor present in the oral secretions of caterpillars. Such an elicitor was isolated from the regurgitant of Spodoptera exigua larvae, identified as N-(17-hydroxylinolenoyl)-L-glutamine, and named volicitin. Here we present details on the procedure that was used to isolate volicitin and the biosasays that demonstrate its potency as an elicitor of maize volatiles that attract parasitoids. With a series of liquid chromatography purification steps, volicitin was separated from all other inactive substances in the regurgitant of larvae of the noctuid moth S. exigua. Maize seedlings that were incubated in very low concentrations of pure natural volicitin released relatively large amounts of terpenoids and became highly attractive to the parasitoid Microplitis croceipes. The identification of this and other insect-derived elicitors should allow us to determine their precise source and function, and better understand the evolutionary history of the phenomenon of herbivore-induced volatile emissions in plants.
Keywords: volicitin; induced plant volatiles; elicitor; parasitoid attractants; Zea mays; Spodoptera exigua; Microplitis croceipes; MICROPLITIS-CROCEIPES CRESSON; PARASITIC WASPS; AIRBORNE; SEMIOCHEMICALS; COTESIA-MARGINIVENTRIS; BETA-GLUCOSIDASE; CHEMICAL; SIGNALS; FLIGHT BEHAVIOR; HOST-LOCATION; PLANTS; LEPIDOPTERA